Le déséquilibre entre les prestations du droit commun et celles des régimes étatiques - O’Donnell, J.V. (Assurances)

(untitled) (HEC Montréal, 1989)
Mr. O'Donnell has authorized us to publish the talk he gave to the Faculty of Law of the University of Ottawa in October 1986, at a conference on the future of bodily injury indemnification. This text has also been published in the Revue générale de droit (vol. 18, no. 1, 1987). The author comments on and compares the main points of government indemnity plans as compared with those of Common Law, where he finds an obvious imbalance. The author looks at the problem in a very clear and interesting manner.